The Price Is Not Always Right : On the Impacts of Commodity Prices on Households (and Countries) - Lederman, Daniel; Porto, Guido (World Bank, Washington, DC, 2016)
This paper provides an overview of the impact that onetime changes in commodity and other prices have on household welfare. It begins with a collection of stylized facts related to commodities based on household survey data from Latin America and Africa. The data uncovers strong commodity dependence on both continents: households typically allocate a large fraction of their budget to commodities, and they often also depend on commodities to earn their income. This income and expenditure dependency suggests sizable impacts and adjustments following commodity price shocks. The article explores these effects with a review of the relevant literature. The authors study consumption and income responses, labor market responses, and spillovers across sectors. The paper provides evidence on the relative magnitudes of various mechanisms through which commodity prices affect household (and national) welfare in developing economies.